Fecundity of Sepioteuthis lessoniana (Cephalopoda:Loliginidae), in the Gulf of Mannar Marine BiosphereReserve: Fecundity of Sepioteuthis lessoniana - M, Kavitha; Geetha Sasikumar (Fishery Technology, 2024)
Sepioteuthis lessoniana is one of the commercially important species, showing genetic differences among its lineages B (Gulf of Mannar) and C (Palk Bay). This study estimated the average fecundity of S. lessoniana from lineages B at 1,043 oocytes, ranging from 308 oocytes in a female, 18.0 cm dorsal mantle length (DML), (11.8 g ovary weight), to 2,563 oocytes in a female, 34.9 cm DML (70.4 g ovaryweight). Larger females exhibited higher fecundity, which increased with DML according to the equation Fecundity=0.2266*DML2.5802. The fecundity-ovary weight relationship followed the equation: Fecundity=21.379+33.131*ovary weight. These findings contribute to our understanding of S. lessoniana stocks from lineage B and their management.